2004
DOI: 10.1103/physreva.70.020302
|View full text |Cite
|
Sign up to set email alerts
|

Multipartite continuous-variable entanglement from concurrent nonlinearities

Abstract: We show theoretically that concurrent interactions in a second-order nonlinear medium placed inside an optical resonator can generate multipartite entanglement between the resonator modes. We show that there is a mathematical connection between this system and van Loock and Braunstein's proposal for entangling N continuous quantum optical variables by interfering with the outputs of N degenerate optical parametric amplifiers (OPA) at a N-port beam splitter. Our configuration, however, requires only one nondege… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 23 publications
0
138
0
2
Order By: Relevance
“…Besides, as an alternative to conventional crystals, a periodically-poled-non-linear waveguide medium and CW laser may be employed, aiming at the production of inherently single-mode (frequency) non-degenerate PDC light. Extension to the tripartite case [49,50,51,52,53,54,55,56,57,58,59] is also in progress and results will be reported elsewhere.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Besides, as an alternative to conventional crystals, a periodically-poled-non-linear waveguide medium and CW laser may be employed, aiming at the production of inherently single-mode (frequency) non-degenerate PDC light. Extension to the tripartite case [49,50,51,52,53,54,55,56,57,58,59] is also in progress and results will be reported elsewhere.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…For quantum key distribution and continuous variable teleportation it has been shown that inseparable three-mode entanglement is useful [6]. This has been demonstrated in optical crystals using consecutive nonlinear optical interactions in resonance [6][7][8][9]. Recently it has been demonstrated, theoretically and experimentally, that three-color tripartite entanglement is possible in an optical parametric oscillator across a wide frequency range [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…We note, however, that in the one-way quantum computing the complexity is shifted from the state control and manipulation to its generation: the different algorithms are realized simply through different measurements. In particular, recent developments in bulk optics [55][56][57][58][59][60], indicate that quantum frequency combs may represent a viable solution for one-way quantum computing. In light of this, our recent results on the generation of wavelength multiplexed photon pairs in microring resonators demonstrate that this is a venue that should be investigated in integrated platforms.…”
Section: Cross-polarized Photon Pair Generationmentioning
confidence: 99%